IMPLEMENTASI MEDIA PEMBELAJARAN BERBASIS TIK PADA PEMBELAJARAN TEMATIK DI SEKOLAH DASAR - Darmansyah; Yanti Fitria; Sinta Medya Agustin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to describe: 1) Describe the implementation of ICT-based learning media in thematic learning in elementary schools; 2) Describe the obstacles to implementing ICT-based learning media in thematic learning in elementary schools; 3) Describe solutions in overcoming obstacles in implementing ICT-based learning media in thematic learning in elementary schools. This type of research is qualitative research using a phenomenological approach. The data collection techniques used were observation, interviews and documentation. Validity of data using triagulation of sources and techniques. The data analysis technique carried out consists of data reduction, data presentation and drawing conclusions. The results of this research are: 1) The implementation of ICT-based learning media in thematic learning can be seen in the implementation of ICT media which has not been fully implemented because teachers have not mastered the technology, the use of ICT media when AKM has not run optimally, most teachers still use books as teaching materials using the method lectures and teachers only display material in the form of writings which only make students feel bored; 2) The obstacles experienced by teachers are that teachers cannot master technology well, ICT facilities and media are limited and teachers are less creative in making teaching materials; 3) The solution obtained by teachers is that teachers can take part in training regarding ICT such as attending seminars, workshops, socialization and so on, complete various ICT-based facilities and media that can support learning activities and teachers take additional material from the internet.